A multicentre retrospective cohort study of ovarian germ cell tumours: Evidence for chemotherapy de-escalation and alignment of paediatric and adult practice. (May 2019) - Newton, C.; Murali, K.; Ahmad, A.; Hockings, H.; Graham, R.; Liberale, V.; Sarker, S.-J.; Ledermann, J.; Berney, D.M.; Shamash, J.; Banerjee, S.; Stoneham, S.; et al.
Abstract: Background: Adult guidelines recommend BEP (bleomycin, etoposide, cisplatin) for all ovarian germ cell tumours, causing debilitating toxicities in young patients who will survive long term. Paediatricians successfully reduce toxicities by using lower bleomycin doses and substituting carboplatin for cisplatin, while testicular and paediatric immature teratomas (ITs) are safely managed with surgery alone. Aim: The aim was to determine whether reduced-toxicity treatment could rationally be extended to patients older than 18 years. Methods: Multicentre cohort study was carried out in four large UK cancer centres over 12 years. Results: One hundred thirty-eight patients were enrolled. Overall survival was 93%, and event-free survival (EFS) was 72%. Neoadjuvant/adjuvant chemotherapy (82% BEP) caused 27 potentially chronic toxicities, and one patient subsequently died from acute lymphoblastic leukaemia. There was no difference in histology, stage or grade in patients ≤/>18 years, and EFS was not different in these age groups (≤18:28% and >18:28%; log-rank P  = 0.96). Histological subtype powerfully predicted EFS (log-rank P  = 4.9 × 10 −7 ). Neoadjuvant/adjuvant chemotherapy reduced future relapse/progression in dysgerminoma (n = 37, chemo:0% vs. no chemo:20%), yolk sac tumour (n = 23, 26.3% vs.75%) and mixed germ cell tumour (n = 32, 40%vs.70%) but not in IT (n = 42, 33% vs.15%). Additionally, we observed no radiological responses to chemotherapy in ITs, pathological IT grade did not predict EFS (univariate hazard ratio 0.82, 95% confidence interval: 0.57–1.19, P  = 0.94) and there were no deaths in this subtype. Conclusion: Survival was excellent but chemotherapy toxicities were severe, implying significant overtreatment. Our data support the extension of reduced-toxicity, paediatric regimens to adults. Our practice-changing findings that IT was chemotherapy resistant and pathological grade uninformative strongly endorse exclusive surgical management of ovarian ITs at all ages. Highlights: BEP (bleomycin, etoposide, cisplatin) chemotherapy caused multiple, severe and even life-threatening toxicities. Ovarian germ cell tumour subtypes were distinct diseases, requiring different management. Immature teratomas (ITs) were chemotherapy resistant. The World Health Organisation pathological grade of ITs did not predict outcome. There was no clinical difference in patients aged ≤/>18 years, but survival was worse in women >40 years ( P  < 0.02).